Recycling glass fiber thermoplastic composites from wind turbine blades. (1st February 2019) - Cousins, Dylan S.; Suzuki, Yasuhito; Murray, Robynne E.; Samaniuk, Joseph R.; Stebner, Aaron P.
Abstract: Thermoplastic resin systems have long been discussed for use in large-scale composite parts but have yet to be exploited by the energy industry. The use of these resins versus their thermosetting counterparts can potentially introduce cost savings due to non-heated tooling, shorter manufacturing cycle times, and recovery of raw materials from the retired part. Because composite parts have high embedded energy, recovery of their constituent materials can provide substantial economic benefit. This study determines the feasibility of recycling composite wind turbine blade components that are fabricated with glass fiber reinforced Elium ® thermoplastic resin. Several experiments are conducted to tabulate important material properties that are relevant to recycling, including thermal degradation, grinding, and dissolution of the polymer matrix to recover the constituent materials. Dissolution, which is a process unique to thermoplastic matrices, allows recovery of both the polymer matrix and full-length glass fibers, which maintain their stiffness (190 N/(mm g)) and strength (160 N/g) through the recovery process. Injection molded regrind material is stiffer (12 GPa compared to 10 GPa) and stronger (150 MPa compared to 84 MPa) than virgin material that had shorter fibers. An economic analysis of the technical data shows that recycling thermoplastic–glass fiber composites via dissolution into their constituent parts is commercially feasible under certain conditions. This analysis concludes that 50% of the glass fiber must be recovered and resold for a price of $0.28/kg. Additionally, 90% of the resin must be recovered and resold at a price of $2.50/kg. Highlights: A thermoplastic wind blade is recycled by dissolution with material recovery. Recycled materials have mechanical properties equivalent to virgin materials. Feasibility of dissolution is contingent on recovered glass fiber value.